Agrobacterium tumefaciens-mediated Transformation of Embryogenic Callus and Somatic Embryos of the Banana cv “Ambon Lumut” (Musa acuminata) - Kusumastuti, Tifa R.; Esyantia, Rizkita R.; Dwivany, Fenny M. (KnE Life Sciences, 2017)
Banana is one of the major fruit crops, though its conventional breeding has limitations, such as sterility and high polyploidy levels. Biotechnological approach using genetic transformation crop for improvement offers an alternative solution. In this study a protocol was developed for establishing genetic transformation from embryogenic callus and somatic embryos of the banana cv Ambon Lumut . Embryogenic callus was obtained in ID4 medium (MS-based medium) supplemented with 1 mg L-1 IAA, 4 mg L-1 2,4D, and 0.03 g L-1 active charcoal. Embryogenic callus was transferred into liquid mediu m to establish somatic embryos. Embryogenic callus and somatic embryos were used for Agrobacterium tumefaciens-mediated transformation. A. tumefaciens strain A GL1, containing pART-TEST7 p lasmid with gfp gene as a reporter and CaM V35S as a promoter, was used for transformations. The embryogenic callus and somatic embryos were transformed using heat-shock method followed by centrifugation (2000 rpm) and co-cult ivation in liquid medium containing acetosyringone (100 M) for 3 days. Results of the GFP analysis showed transient expression from gfp gene reporter in transformed embryogenic callus and somatic embryos. Transformation efficiency in somatic embryos (85,9%) was higher than that in embryogenic callus (32.09%). PCR analysis using CaMV primer showed bands that compatible with CaMV35S promoter at 507 bp. This is a report showing establisment of embryogenic callus and somatic embryo culture transformation by using A. tumefaciens-mediated transformation protocol of the local banana cv Ambon Lumut. This study proved the huge potential for genetic transformation of banana cv Ambon Lumut for crop improvement, such as pest or disease resistance and abiotic factor stress tolerance. Keywords: banana; embryogenic callus; somatic embryos.